Tower of Jewels Illuminated (Pacific Novelty Co.)
On verso: At night great shafts of light from scores of sources strike the main tower and cause tens of thousands of specially prepared glass "Jewels," hung tremulously upon the tower, to flash and scintillate like great diamonds, emeralds and rubies.